THE ROLE OF THE DIMENSIONS OF TACIT KNOWLEDGE IN INCREASING THE EFFICIENCY OF INTERNAL AUDITORS WHEN USING ELECTRONIC AUDITING - Asisst.lect. OMAR KHALID ABDULAMEER ALHABEEB (Scholar Express Journals, 2022)
The study aimed to diagnose the levels of tacit knowledge of auditors and the performance of their work in light of the use of electronic auditing, as well as diagnosing the nature of the impact of the tacit knowledge of auditors in achieving effective performance in government units ,The study was conducted on a group of auditors in some government units in AlMuthanna Governorate, where it was distributed to (65) workers in government units and (60) questionnaires valid for analysis were retrieved with a response rate of (92%). With regard to data analysis, a descriptive statistic method was used to extract frequencies, find percentages, t-test for one sample, Pearson correlation and regression analysis to describe study variables and test the validity of the study hypotheses. A five-point Likud scale was used in the questionnaire, The researcher reached a set of conclusions, the most important of which is the diminishing of tacit knowledge. It is a process through which the performance of workers in economic units is evaluated and measured by comparing them with the main goals and standards of performance set by the top management at a specific time, such as one year, government units need tremendous efforts in Implementing electronic audit in order to further improve the quality of the internal auditors by supporting the human cadres who have professional service and experience The researcher reached the most important recommendations, the necessity of conducting more studies and scientific research related to the application of the tacit knowledge system in all the different economic units, and the need to apply the dimensions of tacit knowledge when applying electronic audit because it will increase the efficiency of the performance of the internal auditors
Keywords: Dimensions of tacit knowledge; Electronic auditing; Internal auditors